Transformasi Penyampaian Firman Dari Mimbar ke Media Sosial - Seri Antonius Tarigan; Remember Sitorus; Rostiar Mitaenjelina Simorangkir (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The advancement of information technology has influenced various aspects of life, including the practice of delivering the Word of God. This article explores the transformation of sermon delivery from conventional pulpits to social media platforms. The primary focus of this study is on how this transformation affects spiritual communication patterns, congregation connectivity, and the sustainability of Christian values in the digital era. Using a phenomenological approach, this article reveals that social media has the potential to expand the reach of ministry but also requires spiritual leaders to adopt strategic and ethical approaches in its use. This transformation brings new challenges, such as the risk of shallow message delivery, the potential for theological distortion, and the limited digital literacy among both ministers and congregants. Social media, with its fast-paced and condensed nature, often encourages the delivery of shorter messages, necessitating caution to ensure that the core message of the Word of God remains intact. Platforms like Facebook, Instagram, and TikTok present unique opportunities to reach the digital generation but also demand a creative, relevant, and Biblically aligned approach. Contextualizing the message becomes key, enabling the Word of God to be delivered in an engaging and easily understood format without diminishing its profound meaning.